2014
DOI: 10.17306/j.afs.2014.1.9
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of nutritional and biochemical parameters in spontaneously hypertensive rats following antihypertensive treatment

Abstract: Introduction. One side effect of antihypertensive drugs is their impact on nutritional status and metabolism. The purpose of this study was to assess the nutritional and biochemical parameters in spontaneously hypertensive rats following treatment with antihypertensive drugs. Material and methods. The experiment was performed on 50 male spontaneously hypertensive rats (SHR), which were assigned to fi ve groups: control (C), with perindopril (PR), with metoprolol (MT), with indapamide (ID), and with amlodipine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 24 publications
(22 reference statements)
0
5
0
Order By: Relevance
“…Moreover, the decrease in zinc is accompanied by an increase in glucose serum levels [2]. In our experimental study, we observed that treatment with indapamide and amlodipine was associated with increased red blood cell counts and hematocrit values in the serum of spontaneously hypertensive rats [3]. In patients, high hematocrit could reflect the increase in red blood cell mass resulting from the reduction in plasma volume due to treatment with thiazide-type diuretics.…”
mentioning
confidence: 74%
“…Moreover, the decrease in zinc is accompanied by an increase in glucose serum levels [2]. In our experimental study, we observed that treatment with indapamide and amlodipine was associated with increased red blood cell counts and hematocrit values in the serum of spontaneously hypertensive rats [3]. In patients, high hematocrit could reflect the increase in red blood cell mass resulting from the reduction in plasma volume due to treatment with thiazide-type diuretics.…”
mentioning
confidence: 74%
“…Similar results were also obtained in another study performed on hypertensive animals. [ 17 ] In the literature, there is no information about changes in RBC quantity or volume in SHRs under the influence of amlodipine. On the other hand, it is well known that amlodipine has a slight diuretic effect, which may cause a reduction in plasma volume.…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, it needs to be stressed that already enrichment of the product with a 10% addition of dried oyster mushroom caused a significant restoration of systemic iron level in those animals. Suliburska [23,24] expressed an opinion that products enriched with Fe are better sources of potentially available Fe than products not enriched with this nutrient, but the sorption of minerals depended on the dietary fibre source, adsorbent type, processing method, pH and temperature of the medium, as well as on the metal. Regula and Gramza-Michalowska [25] observed in in vitro experiments, maximum sorption values at pH = 8.7 for Fe in bread with 10% and 20% dried mushrooms added (15% and 17%, respectively).…”
Section: Discussionmentioning
confidence: 99%